Tempered glass plate, method for producing tempered glass plate, and glass plate for strengthening

By adding specific components to the glass and ion exchange treatment, a surface compression stress layer is formed, which solves the problem of insufficient mechanical strength and transmittance of the existing reinforced glass plate, and achieves high-performance and low-cost reinforced glass plate manufacturing.

CN119522198APending Publication Date: 2025-02-25NIPPON ELECTRIC GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055826.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-16
Filing Date
2023-08-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing reinforced glass plates have shortcomings in terms of mechanical strength and transmittance, especially when crystallization is not carried out, it is difficult to take into account both high mechanical strength and high transmittance, and at the same time, the manufacturing cost is high.

Method used

A glass containing components such as SiO2, Al2O3, Li2O, Na2O, etc. is composed of a glass, and a surface compression stress layer is formed through ion exchange treatment to optimize the mechanical properties and transmittance of the glass.

Benefits of technology

It is achieved to improve the mechanical strength and transmittance of the reinforced glass plate without including crystalline material, reduce manufacturing costs, and improve the overall performance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522198A_ABST
    Figure CN119522198A_ABST
Patent Text Reader

Abstract

The tempered glass plate according to the present invention is characterized by comprising, as a glass composition, 50 to 85% by mole of SiO2, 1 to 25% by mole of Al2O3, 0 to 15% by mole of B2O3, 0 to 20% by mole of Li2O, 0 to 25% by mole of Na2O, 0 to 20% by mole of K2O, 0 to 10% by mole of ZnO, 0 to 15% by mole of P2O5, 0 to 10% by mole of ZrO2, 0 to 0.30% by mole of SnO2, 1 to 30% by mole of [Li2O] + [Na2O], 1 to 25% by mole of [Li2O] + [MgO], and 0.5 to 30% by mole of [MgO] + [CaO] + [SrO] + [BaO].
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a tempered glass plate and a method for producing the same, and in particular to a tempered glass plate suitable for use as a cover glass of a touch panel display of a mobile phone, a digital camera, a PDA (mobile terminal), etc., a method for producing the tempered glass plate, and a tempered glass plate. Background Art

[0002] In applications such as mobile phones (especially smart phones), digital cameras, and PDAs (mobile terminals), ion-exchange-treated tempered glass plates are used as cover glasses for touch panel displays (see Patent Document 1).

[0003] The properties required of cover glass include, for example, (1) high mechanical strength, (2) high transparency, and (3) low manufacturing cost. Mechanical strength refers to the strength properties of glass determined by the mechanical properties and strengthening properties of glass. Here, mechanical properties mainly refer to properties related to the strength of glass determined by the glass composition, such as fracture toughness values. Strengthening properties refer to properties related to the strength of glass that are subsequently imparted to the formed glass through ion exchange treatment, such as compressive stress values ​​on the glass surface.

[0004] The ion-exchange treated tempered glass sheet has a compressive stress layer on the surface, and thus has a characteristic that the formation and growth of surface cracks are easily suppressed (see Patent Document 1).

[0005] However, the conventional tempered glass sheet disclosed in Patent Document 1 tends to have low mechanical properties such as fracture toughness, and therefore it is difficult to improve the mechanical strength.

[0006] In recent years, the use of crystallized glass subjected to ion exchange treatment in cover glass has been studied (see Patent Document 2). Since the crystallized glass contains crystals, it has high mechanical properties. Therefore, the strengthened crystallized glass has high mechanical strength.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-83045

[0010] Patent Document 2: International Publication No. 2019 / 230889 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, since crystallized glass contains crystals, its transmittance tends to be lower than that of amorphous glass, and when used as a cover glass, the visibility and color expression of a display may be reduced.

[0013] In addition, since crystallized glass needs to be heated at a high temperature in order to precipitate crystals, there is a problem that the production cost tends to increase.

[0014] In view of the above situation, the present invention has a technical problem of providing a strengthened glass plate having higher mechanical strength than a conventional amorphous strengthened glass plate even without undergoing a crystallization treatment, that is, even without containing crystalline substances, and having higher transmittance than a crystallized chemically strengthened glass plate, as well as a method for manufacturing a strengthened glass plate and a strengthened glass plate capable of obtaining the same at low cost.

[0015] Means of solving the problem

[0016] The tempered glass plate of the present invention is characterized in that it is a tempered glass plate having a compressive stress layer on the surface, and contains SiO 2 50~80%,Al 2 O 3 1~25%, B 2 O 3 0~15%,Li 2 O 0~20%, Na 2 O 0~25%, K 2 O 0~20%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%,[Li 2 O]+[Na 2 O] 1~30%,[Li 2 O] + [MgO] 1 to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.5 to 30%. Here, [Li 2 O]+[Na 2 O] refers to Li 2 O and Na 2 The total amount of O, [Li 2 O]+[MgO] means Li 2 The total amount of O and MgO, [MgO] + [CaO] + [SrO] + [BaO] refers to the total amount of the contents of MgO, CaO, SrO and BaO.

[0017] The tempered glass plate of the present invention is a tempered glass plate having a compressive stress layer on the surface, and the glass composition preferably contains SiO 2 52~80%,Al 2 O 3 11.5~25%, B 2 O 3 0~15%,Li 2 O 7~20%, Na 2 O 0.5~25%, K 2 O 0~20%, MgO 0~20%, CaO 0~10%, SrO 0~10%, BaO 0~10%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%, [MgO] + [CaO] + [SrO] + [BaO] 6.5~30%.

[0018] According to such a configuration, the strain point, Vickers hardness, Young's modulus, and fracture toughness of the tempered glass sheet can be easily increased.

[0019] Furthermore, the tempered glass plate of the present invention preferably contains MgO as a glass composition, and the content of MgO is preferably 6.5 to 20 mol %.

[0020] According to such a configuration, the high-temperature viscosity can be easily reduced, the meltability and formability can be improved, and the strain point, Vickers hardness, Young's modulus, and fracture toughness can be improved.

[0021] In addition, the tempered glass plate of the present invention preferably has a molar ratio of [RO] / [R 2 Here, "[RO]" is the total amount of alkaline earth metal oxides ([MgO] + [CaO] + [SrO] + [BaO]), "[R 2 O]” is the total amount of alkali metal oxides ([Li 2 O]+[Na 2 O]+[K 2 O]). Therefore, “[RO] / [R 2 "(O]" is a value obtained by dividing the total amount of alkaline earth metal oxides by the total amount of alkali metal oxides.

[0022] According to such a configuration, formability, devitrification resistance, and mechanical properties can be easily improved.

[0023] In addition, the tempered glass plate of the present invention preferably contains substantially no crystals, and has a transmittance of 85% or more at a wavelength of 400 nm when converted to a thickness of 0.6 mm. Here, "substantially contains no crystals" means that the content of crystals in the tempered glass plate is 0.01% by mass or less.

[0024] According to such a configuration, it is easy to obtain glass with high visibility and color expression.

[0025] Furthermore, the tempered glass plate of the present invention preferably has a Young's modulus of 76 GPa or more.

[0026] According to such a configuration, when the thickness of the tempered glass plate is small, the cover glass is less likely to bend.

[0027] In addition, the tempered glass plate of the present invention preferably has a fracture toughness K1c of 0.78 MPa·m 0.5 above.

[0028] According to such a configuration, it is possible to obtain a tempered glass plate that is unlikely to self-explode or that is unlikely to be explosively shattered when exploded.

[0029] In addition, it is preferred that the tempered glass plate of the present invention is a plate with a thickness of 0.01 to 2.0 mm, the compressive stress value CS of the outermost surface of the compressive stress layer is 200 to 1200 MPa, and the stress depth DOC of the compressive stress layer is 3 to 200 μm. Here, the "outermost surface compressive stress value" and "stress depth" refer to, for example, when the compressive stress is caused by Na ions introduced by ion exchange, the value measured based on the phase difference distribution curve observed using the scattered light photoelastic stress meter SLP-2000 (manufactured by Orihara Seisakusho Co., Ltd.), or when the compressive stress is caused by K ions introduced by ion exchange, the value measured based on the phase difference distribution curve observed using the surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.). Then, the stress depth refers to the depth at which the stress value becomes 0. In addition, in the calculation of the stress characteristics of each sample, the refractive index and the photoelastic constant are used. The refractive index uses the value measured by the V block method. The photoelastic constant uses the value measured by the optical heterodyne measurement method.

[0030] According to such a configuration, a tempered glass plate having high strength can be easily obtained.

[0031] The tempered glass plate of the present invention is preferably in the form of a plate with a thickness of 0.35 to 2.0 mm, a stress depth DOC of the compressive stress layer of 50 to 170 μm, and a compressive stress value CS30 at a depth of 30 μm from the outermost surface of 25 to 400 MPa.

[0032] According to such a configuration, a tempered glass plate that is difficult to break when dropped can be obtained.

[0033] In addition, the tempered glass plate of the present invention preferably has a high temperature viscosity of 10 2.5 dPa·s is 1680°C or lower. 2.5 The temperature under dPa·s” can be measured, for example, by a platinum ball pulling method.

[0034] According to such a structure, the molten glass can be easily formed into a plate shape.

[0035] Furthermore, the tempered glass plate of the present invention preferably contains Cl as a glass composition, and the content of Cl is preferably 0.02 mol % or more.

[0036] According to such a configuration, the bubble diameter in the molten glass can be easily enlarged, and a high clarification effect can be obtained.

[0037] The tempered glass plate of the present invention preferably contains MoO as a glass composition. 3 , and MoO 3 The content is 0.0001 mol % or more.

[0038] According to such a configuration, the tempered glass plate easily absorbs ultraviolet rays, and degradation of elements inside the device due to ultraviolet rays can be suppressed.

[0039] The tempered glass plate of the present invention is a tempered glass plate having a compressive stress layer on the surface, and the glass composition preferably contains SiO 2 60~70%,Al 2 O 3 3~20%, B 2 O 3 0~1%, Li 2 O 0~10%, Na 2 O 10~25%, K 2 O 0~5%, MgO 5~20%, CaO 0~1%, SrO 0~10%, BaO 0~10%, ZnO 0~10%, P 2 O 5 0~4.7%, [MgO] + [CaO] + [SrO] + [BaO] 5~30%.

[0040] According to such a configuration, it is easy to suppress a decrease in the liquidus viscosity of the tempered glass sheet.

[0041] The tempered glass plate of the present invention is a tempered glass plate having a compressive stress layer on the surface, and the glass composition preferably contains SiO 2 65~82%,Al 2 O 3 5~16%, B 2 O3 0~10%, Li 2 O 0~10%, Na 2 O 5~25%, K 2 O 0~5%, MgO 0~10%, CaO 0~6%, SrO 0~5%, BaO 0~5%, ZnO 0~10%, P 2 O 5 0~4.7%,[Li 2 O]+[Na 2 O] 5~20%, [MgO] + [CaO] + [SrO] + [BaO] 1~10%.

[0042] According to such a structure, it is easy to obtain a tempered glass plate with high acid resistance, especially high hydrofluoric acid resistance. In addition, by improving the acid resistance, for example, after chemical etching treatment of the tempered glass plate, the surface of the tempered glass plate can be made to have fewer micro-concavities and convexities. As a result, the strength of the tempered glass plate can be improved.

[0043] The method for producing a tempered glass plate of the present invention is characterized by comprising the following steps: a step of preparing a tempered glass plate, wherein the tempered glass plate contains SiO in a mol% glass composition. 2 50~80%,Al 2 O 3 1~25%, B 2 O 3 0~15%,Li 2 O 0~20%, Na 2 O 0~25%, K 2 O 0~20%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%,[Li 2 O]+[Na 2 O] 1~30%,[Li 2 O] + [MgO] 1 to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.5 to 30%; an ion exchange step, wherein the strengthened glass plate is subjected to ion exchange treatment to obtain a strengthened glass plate having a compressive stress layer on the surface.

[0044] The tempered glass plate of the present invention is characterized in that, as a glass composition, it contains SiO in mol%. 2 50~80%,Al 2 O 3 1~25%, B 2O 3 0~15%,Li 2 O 0~20%, Na 2 O 0~25%, K 2 O 0~20%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%,[Li 2 O]+[Na 2 O] 1~30%,[Li 2 O] + [MgO] 1 to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.5 to 30%.

[0045] Effects of the Invention

[0046] According to the present invention, a tempered glass plate having mechanical strength and transmittance suitable for a cover glass, a method for producing a tempered glass plate, and a tempered glass plate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a schematic diagram illustrating the stress distribution of a tempered glass sheet (stress distribution in the thickness direction of the glass sheet) in which ion exchange of Li ions and Na ions in a molten salt has been performed. DETAILED DESCRIPTION

[0048] The tempered glass plate and tempered glass plate of the present invention contain SiO 2 50~80%,Al 2 O 3 1~25%, B 2 O 3 0~15%,Li 2 O 0~20%, Na 2 O 0~25%, K 2 O 0~20%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%,[Li 2 O]+[Na 2 O] 1~30%,[Li 2O] + [MgO] 1 to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.5 to 30%. The reasons for limiting the content range of each component are shown below. In the description of the content range of each component, % means molar % unless otherwise specified.

[0049] SiO 2 It is a component that forms the glass network. 2 If the content of SiO is too low, it will be difficult to vitrify, and the thermal expansion coefficient will tend to become too high, which will reduce the thermal shock resistance. In addition, the hydrofluoric acid resistance may be reduced. Therefore, SiO 2 The suitable lower limit range is 50% or more, 52% or more, 55% or more, 57% or more, 58% or more, 58.5% or more, 59% or more, 60% or more, 61% or more, 62% or more, 62.5% or more, 63% or more, 63.5% or more, 64.0% or more, 64.5% or more, and especially 65% ​​or more. On the other hand, if SiO 2 If the content of SiO is too high, the meltability and formability will be easily reduced. In addition, the thermal expansion coefficient becomes too low and it is difficult to match the thermal expansion coefficient of the surrounding materials. 2 Suitable upper ranges are 85% or less, 82% or less, 80% or less, 75% or less, 73% or less, 72% or less, 71% or less, 70.5% or less, 70% or less, 69.5% or less, 69% or less, 68.5% or less, 68% or less, 67.8% or less, 67.5% or less, 67.2% or less, and especially 67% or less.

[0050] Al 2 O 3 It is a component that improves ion exchange performance, and also a component that improves strain point, Young's modulus, fracture toughness, and Vickers hardness. 2 O 3 The suitable lower limit range of Al is 1% or more, 3% or more, 5% or more, 7% or more, 7.2% or more, 7.5% or more, 7.8% or more, 8% or more, 8.2% or more, 8.5% or more, 9% or more, 9.2% or more, 9.4% or more, 9.5% or more, 9.8% or more, 10.0% or more, 10.3% or more, 10.5% or more, 10.8% or more, 11% or more, 11.2% or more, 11.4% or more, 11.5% or more, 11.6% or more, 11.7% or more, 11.8% or more, and particularly 12% or more. On the other hand, if Al 2 O 3If the content of is too much, the high temperature viscosity increases, and the melting and forming properties are easily reduced. In addition, devitrified crystals are easily precipitated in the glass, and it is difficult to form it into a plate by overflow down-drawing method. In particular, when an alumina refractory is used as a forming body refractory, when it is formed into a plate by overflow down-drawing method, devitrified crystals of spinel are easily precipitated at the interface with the alumina refractory. In addition, the acid resistance is reduced, and it is difficult to apply it to the acid treatment process. Therefore, Al 2 O 3 Suitable upper ranges are 25% or less, 23% or less, 21% or less, 20.5% or less, 20% or less, 19.8% or less, 19.5% or less, 19.0% or less, 18.5% or less, 18% or less, 17.5% or less, 17% or less, 16.5% or less, 16% or less, 15.5% or less, 15.2% or less, 15% or less, 14.9% or less, 14.7% or less, 14.5% or less, 14.3% or less, 14% or less, 13.5 or less, and especially 13% or less.

[0051] B 2 O 3 It is a component that reduces high temperature viscosity and density, stabilizes the glass, makes it difficult to precipitate crystals, and reduces the liquidus temperature. It is also a component that increases the binding force of cations on oxygen electrons and reduces the basicity of the glass. 2 O 3 If the content of is too low, the stress depth DOC in the ion exchange between the Li ions contained in the glass and the Na ions in the molten salt becomes too deep, resulting in a tendency for the compressive stress value from the outermost surface to a predetermined depth (5 to 50 μm) to decrease. In addition, the glass becomes unstable and the resistance to devitrification may also decrease. In addition, if the basicity of the glass becomes too high, the O 2 The release amount is reduced, the foaming property is reduced, and foam may remain in the glass when it is formed into a sheet. 2 O 3 The suitable lower limit range is 0% or more, 0.10% or more, 0.15% or more, 0.20% or more, 0.30% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, 3.5% or more, 4% or more, and especially 4.5% or more. On the other hand, if B 2 O 3 If the content of B is too high, the efficiency of ion exchange between Li ions contained in the glass and Na ions in the molten salt is likely to decrease, the diffusion of Na ions is likely to decrease, and the stress depth may become shallower. In addition, Young's modulus and fracture toughness are reduced, and it may be easy to explode or explode the glass. 2 O 3The suitable upper limit range is 15% or less, 14.5% or less, 14% or less, 13.5% or less, 13% or less, 12.5% ​​or less, 12% or less, 11.5% or less, 11% or less, 10.5% or less, 9.5% or less, 9% or less, 8.5% or less, 8% or less, 7.5% or less, 7% or less, 6.5% or less, 6% or less, especially 5.5% or less. When paying attention to improving Young's modulus and fracture toughness, the suitable content is 0-1%, 0-0.8%, especially 0-0.5%.

[0052] Li 2 O is an ion exchange component, and is particularly effective in exchanging Li ions contained in the glass with Na ions in the molten salt, and is used to obtain a deep stress depth. 2 O is a component that reduces high temperature viscosity, improves meltability and formability, and increases Young's modulus. 2 The suitable lower limit range of O is 0% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, 3.5% or more, 4% or more, 4.3% or more, 4.5% or more, 4.7% or more, 5% or more, 5.2% or more, 5.5% or more, 5.8% or more, 6.2% or more, 6.5% or more, 6.8% or more, 7.0% or more, 7.5% or more, and especially 8% or more. On the other hand, if Li 2 If the content of O is too high, the liquidus temperature rises and devitrified crystals are easily precipitated in the glass, making it difficult to form the glass into a sheet by overflow down-drawing or the like. 2 Suitable upper ranges for O are 20% or less, 18% or less, 17% or less, 15% or less, 13% or less, 12% or less, 11.5% or less, 11% or less, 10.5% or less, 10% or less, 9.8% or less, 9.5% or less, 9.3% or less, 9% or less, 8.8% or less, and especially 8.5% or less.

[0053] Na 2 O is an ion exchange component and also a component that reduces high temperature viscosity and improves meltability and formability. 2 O is a component that improves the resistance to devitrification, and in particular, a component that suppresses devitrification that occurs during the reaction with alumina-based refractory. 2The suitable lower limit range of O is 0% or more, 0.1% or more, 0.2% or more, 0.3% or more, 0.5% or more, 0.7% or more, 0.8% or more, 1% or more, 1.2% or more, 1.3% or more, 1.4% or more, 1.5% or more, 1.8% or more, 2% or more, 2.1% or more, 2.2% or more, 2.3% or more, 2.5% or more, 2.8% or more, and especially 3% or more. On the other hand, if Na 2 If the content of O is too high, the thermal expansion coefficient becomes too high, and the thermal shock resistance is likely to decrease. In addition, the component balance of the glass composition is disrupted, and the resistance to devitrification may decrease. Therefore, Na 2 The suitable upper limit range of O is 25% or less, 21% or less, 20% or less, 19% or less, 18% or less, 15% or less, 13% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7.5% or less, 7% or less, 6.5% or less, 6% or less, 5.8% or less, 5.5% or less, 5.2% or less, and particularly 5% or less. In addition, when the ion exchange of Na ions in the glass and K ions in the molten salt is emphasized, Na 2 The suitable lower limit range of O is 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, and especially 10% or more.

[0054] K 2 O is a component that reduces high temperature viscosity and improves meltability and formability. It is also a component that increases stress depth. Therefore, K 2 The suitable lower limit range of O is 0% or more, 0.01% or more, 0.02% or more, 0.03% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, and especially 0.5% or more. On the other hand, if K 2 If the content of O is too high, the thermal expansion coefficient will increase, and the thermal shock resistance may decrease. In addition, the compressive stress value of the outermost surface is likely to decrease. Therefore, K 2 Suitable upper ranges for O are 20% or less, 18% or less, 15% or less, 12% or less, 10% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.5% or less, 1% or less, and especially less than 1%.

[0055] MgO is a component that reduces high temperature viscosity, improves meltability and formability, and improves strain point, Vickers hardness, Young's modulus and fracture toughness. It is a component that has a large effect on improving ion exchange performance among alkaline earth metal oxides. Therefore, the appropriate lower limit range of MgO is 0% or more, 0.1% or more, 0.5% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, 3.5% or more, 4% or more, 4.5% or more, 5% or more, 5.2% or more, 5.5% or more, 5.8% or more, 6% or more, 6.1% or more, 6.2% or more, 6.3% or more, 6.4% or more, and especially 6.5% or more. On the other hand, if the content of MgO is too much, the devitrification resistance is easily reduced, and it is particularly difficult to suppress the devitrification that occurs in the reaction with alumina-based refractory. Therefore, a suitable upper range of MgO is 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10.8% or less, 10.5% or less, 10.4% or less, 10.3% or less, 10.2% or less, 10.1% or less, and particularly 10% or less.

[0056] Compared with other components, CaO is a component that reduces high temperature viscosity, improves solubility and formability, and improves strain point and Vickers hardness without reducing devitrification resistance. However, if the content of CaO is too much, the ion exchange performance is reduced, or the ion exchange solution may be degraded during ion exchange treatment. Therefore, the content of CaO is preferably 0 to 12%, 0 to 10%, 0 to 9%, 0 to 8%, 0 to 7%, 0 to 6%, 0 to 5.5%, 0 to 5%, 0 to 4.5%, 0 to 4%, 0 to 3.5%, 0 to 3%, 0 to 2%, and especially 0 to 1%.

[0057] SrO is a component that reduces high temperature viscosity, improves solubility and formability, and increases strain point and Young's modulus. However, if its content is too high, in addition to being easy to hinder ion exchange reaction, density and thermal expansion coefficient will also increase unreasonably, and glass is easy to devitrify. Therefore, the SrO content is preferably 0-12%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, and particularly 0-1%.

[0058] BaO is a component that reduces high temperature viscosity, improves solubility and formability, and increases strain point and Young's modulus. However, if its content is too high, it will not only easily hinder ion exchange reaction, but also increase density and thermal expansion coefficient unreasonably, and glass will easily lose clarity. Therefore, the content of BaO is preferably 0-12%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, and particularly 0-1%.

[0059] ZnO is a component that improves ion exchange performance, and in particular, a component that has a large effect of improving the compressive stress value of the outermost surface of the compressive stress layer. In addition, it is still a component that does not significantly reduce the low-temperature viscosity and reduces the high-temperature viscosity. On the other hand, if the content of ZnO is too much, there is a tendency for glass phase separation, or a decrease in devitrification resistance, or a density increase, and a shallower stress depth. Therefore, the appropriate upper limit range of ZnO is 10% or less, 8% or less, 7% or less, 6% or less, 5.5% or less, 5.2% or less, 5% or less, 4.5% or less, and particularly 4% or less. Suitable lower limit ranges of ZnO are 0% or more, 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.7% or more, 1% or more, 1.1% or more, 1.2% or more, 1.5% or more, 1.8% or more, 2.0% or more, 2.1% or more, 2.2% or more, 2.5% or more, 2.8% or more, 3.0% or more, 3.1% or more, 3.2% or more, and especially 3.5% or more.

[0060] P 2 O 5 It is a component that improves ion exchange performance, especially a component that deepens stress depth. It is also a component that improves acid resistance. It is also a component that increases the binding force of cations on oxygen electrons and reduces the basicity of glass. However, if P 2 O 5 If the content of P is too high, the glass is prone to phase separation and water resistance is likely to decrease. In addition, the stress depth DOC in the ion exchange between Li ions contained in the glass and Na ions in the molten salt becomes too deep, resulting in a tendency for the compressive stress value from the outermost surface to a predetermined depth (5 to 50 μm) to decrease. Therefore, P 2 O 5 The suitable upper limit range of P is 15% or less, 12% or less, 10% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4.7% or less, 4.5% or less, 4% or less, and especially 3.5% or less. On the other hand, if P 2 O 5 If the content of is too low, the ion exchange performance may not be fully exerted. In addition, the glass becomes unstable and the resistance to devitrification may also decrease. In addition, if the basicity of the glass is too high, the reaction of the clarifier may cause the O2 The release amount is reduced, the foaming property is reduced, and foam may remain in the glass during sheet forming. 2 O 5 The suitable lower limit range is 0% or more, 0.01% or more, 0.02% or more, 0.03% or more, 0.05% or more, and especially 0.1% or more.

[0061] SnO 2 SnO is a clarifier and a component that improves ion exchange performance, but if its content is too high, the devitrification resistance is likely to decrease. 2 The suitable lower limit range is 0% or more, 0.001% or more, 0.002% or more, 0.005% or more, 0.007% or more, and especially 0.010% or more, and the suitable upper limit range is 0.30% or less, 0.27% or less, 0.25% or less, 0.20% or less, 0.18% or less, 0.15% or less, 0.12% or less, 0.10% or less, 0.09% or less, 0.08% or less, 0.07% or less, 0.06% or less, 0.05% or less, 0.047% or less, 0.045% or less, 0.042% or less, 0.040% or less, 0.038% or less, 0.035% or less, 0.032% or less, 0.030% or less, 0.025% or less, 0.020% or less, and especially 0.015% or less.

[0062] Cl is a clarifier. Especially through the reaction with SnO 2 When used together, the bubble diameter in the glass is easily expanded and the clarification effect is easily exerted. On the other hand, if its content is too much, it will be a component that has an adverse effect on the environment and equipment. Therefore, the appropriate lower limit range of Cl is 0.001% or more, 0.005% or more, 0.008% or more, 0.010% or more, 0.015% or more, 0.018% or more, 0.019% or more, 0.020% or more, 0.023% or more, 0.025% or more, 0.027% or more, 0.030% or more, 0.035% or more, 0.040% or more, 0.050% or more, 0.07% or more, 0.09% or more, especially 0.10% or more, and the appropriate upper limit range is 0.3% or less, 0.2% or less, 0.17% or less, 0.15% or less, especially 0.12% or less. In addition, if the Cl content is too little, SnO must be increased in order to ensure the desired clarification. 2 The amount may reduce the devitrification resistance.

[0063] MoO 3 It is a component that absorbs ultraviolet light (light with a wavelength of 200 to 300 nm). 3, it is possible to suppress the degradation of the internal components of a device using the tempered glass plate of the present invention as a cover glass due to ultraviolet rays. 3 It can be introduced by adding a trace amount to the raw material batch, but when the raw material batch is melted by electric melting heating, it can also be introduced by dissolving it from the Mo electrode. By adopting electric melting, the water content in the glass can be reduced. If the water content in the glass is reduced, the liquid phase viscosity and softening point will increase, which can improve the resistance to devitrification and heat resistance of the glass. In addition, as the strain point increases, stress relaxation is less likely to occur, and a high compressive stress value can be maintained. If MoO 3 If the content is too low, it will be difficult to introduce MoO by electrofusion. 3 Therefore, MoO 3 The suitable lower limit of the content of MoO is, in mole %, 0% or more, 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.0008% or more, 0.001% or more, 0.0012% or more, 0.0015% or more, and particularly 0.002% or more. On the other hand, if MoO 3 If the content of MoO is too high, the transmittance of the cover glass will be easily reduced. 3 The suitable upper limit range of the content, in mol %, is 0.02% or less, 0.018% or less, 0.015% or less, 0.012% or less, 0.01% or less, 0.008% or less, 0.007% or less, 0.006% or less, 0.005% or less, and especially less than 0.004%.

[0064] Li 2 O and Na 2 The total amount of O content is [Li 2 O]+[Na 2 The suitable lower limit range of [Li O] is 1% or more, 3% or more, 5% or more, 6% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more, 8.8% or more, 9% or more, 9.5% or more, 9.7% or more, and especially 10% or more. 2 O]+[Na 2 O] is too little, ion exchange is difficult. On the other hand, if [Li 2 O]+[Na 2 If the amount of [Li O] is too large, the chemical resistance may decrease. 2 O]+[Na 2 The suitable upper limit range of O] is 30% or less, 28% or less, 25% or less, 23% or less, and especially 20% or less.

[0065] Li 2 The total amount of O and MgO is [Li 2The suitable lower limit of [Li O] + [MgO] is 1% or more, 3% or more, 5% or more, 6% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more, 8.8% or more, 9% or more, 9.5% or more, 9.7% or more, and especially 10% or more. 2 O] + [MgO] is too little, it is difficult to improve mechanical properties such as Young's modulus and fracture toughness. In addition, high temperature viscosity increases, and meltability and formability may decrease. On the other hand, if [Li 2 If the amount of [Li O] + [MgO] is too large, the devitrification resistance may be reduced. 2 The suitable upper limit range of [O] + [MgO] is 25% or less, 23% or less, 20% or less, and particularly 18% or less.

[0066] The appropriate lower limit range of the total amount of MgO, CaO, SrO and BaO, i.e., [MgO] + [CaO] + [SrO] + [BaO], is 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1% or more, 1.5% or more, 2% or more, 3% or more, 3.5% or more, 4% or more, 4.5% or more, 5% or more, 6% or more, 6.5% or more, 7% or more, 7.5% or more, and especially 8% or more. If [MgO] + [CaO] + [SrO] + [BaO] is too little, it is difficult to increase the strain point, Vickers hardness, Young's modulus and fracture toughness. In addition, the high temperature viscosity increases, and the meltability and formability may decrease. On the other hand, if [MgO] + [CaO] + [SrO] + [BaO] is too much, the devitrification resistance may decrease. Therefore, the suitable upper limit range of [MgO] + [CaO] + [SrO] + [BaO] is less than 30%, less than 28%, less than 25%, less than 24%, less than 22%, less than 20%, less than 18%, less than 15%, less than 12%, and especially less than 10%.

[0067] B 2 O 3 The total amount of MgO and CaO is [B 2 O 3 The suitable lower limit of [MgO]+[CaO] is 0.1% or more, 0.5% or more, 0.8% or more, 1% or more, 2% or more, 3% or more, 3.5% or more, 4% or more, 5% or more, 6% or more, 6.5% or more, and especially 7% or more. 2 O 3 If [B] + [MgO] + [CaO] is too small, it will be difficult to lower the softening point. 2 O 3If the amount of [MgO]+[CaO]+[MgO]+[CaO] is too large, the glass will become unstable and the devitrification resistance may be reduced. 2 O 3 The suitable upper limit range of ]+[MgO]+[CaO] is less than 30%, less than 28%, less than 25%, less than 24%, less than 22%, less than 20%, and especially less than 18%.

[0068] Li 2 O、Na 2 O and K 2 The total amount of O content is [Li 2 O]+[Na 2 O]+[K 2 The suitable lower limit of [Li O] is 7% or more, 7.5% or more, 8% or more, 8.5% or more, 8.8% or more, 9% or more, 9.5% or more, 9.7% or more, and especially 10% or more. 2 O]+[Na 2 O]+[K 2 O] is too small, the efficiency of ion exchange tends to decrease, making it difficult to lower the softening point. 2 O]+[Na 2 O]+[K 2 If the amount of [Li O] is too large, the chemical resistance may be reduced. 2 O]+[Na 2 O]+[K 2 The suitable upper limit range of O] is 30% or less, 28% or less, 25% or less, 23% or less, 20% or less, and especially 18% or less.

[0069] Molar ratio [R 2 O] / [Al 2 O 3 The suitable lower limit range of [R 2 O] / [Al 2 O 3 ] is too small, the efficiency of ion exchange tends to decrease. On the other hand, the molar ratio[R 2 O] / [Al 2 O 3 ] is too large, the efficiency of ion exchange is likely to decrease. Therefore, the molar ratio[R 2 O] / [Al 2 O 3 The suitable upper limit range of [R 2O] / [Al 2 O 3 ]" means that Li 2 O、Na 2 O and K 2 The total amount of O content [R 2 O], divided by Al 2 O 3 The value of the content.

[0070] Molar ratio [RO] / [R 2 The suitable lower limit range of [RO] is 0.5 or more, 0.52 or more, 0.55 or more, 0.58 or more, 0.6 or more, 0.62 or more, 0.65 or more, 0.68 or more, 0.70 or more, 0.72 or more, 0.75 or more, 0.78 or more, especially 0.8 or more. 2 O] is too small, the strain point, Vickers hardness, Young's modulus and fracture toughness may decrease. On the other hand, if the molar ratio [RO] / [R 2 If the molar ratio [RO] / [R 2 The suitable upper limit range of O] is 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, and particularly 1 or less.

[0071] Molar ratio [Al 2 O 3 ] / ([R 2 The upper limit range of [AlO] + [RO] is preferably 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1 or less, and particularly 0.9 or less. 2 O 3 ] / ([R 2 O] + [RO]) is too large, the high temperature viscosity increases, and the meltability and formability are likely to decrease. On the other hand, if [Al 2 O 3 ] / ([R 2 If [AlO] + [RO]) is too small, the liquidus temperature and liquidus viscosity may decrease. 2 O 3 ] / ([R 2 The appropriate lower limit of the molar ratio [AlO] + [RO] is 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, and particularly 0.4 or more. 2 O 3 ] / ([R 2 O] + [RO]) means that Al 2 O 3The content of MgO is divided by the total content of MgO, CaO, SrO and BaO [RO] and the content of Li 2 O、Na 2 O and K 2 The total amount of O content [R 2 O]total value.

[0072] Molar ratio [Na 2 O] / [Li 2 The suitable upper limit range of [NaO] is 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.58 or less, 0.55 or less, 0.52 or less, 0.5 or less, 0.48 or less, 0.45 or less, 0.43 or less, and especially 0.4 or less. 2 O] / [Li 2 O] is too large, the efficiency of ion exchange between Li ions contained in the glass and Na ions in the molten salt tends to decrease. On the other hand, if the molar ratio [Na 2 O] / [Li 2 If the molar ratio [NaO] is too small, the high temperature viscosity increases, and the meltability and formability may decrease. In addition, the devitrification resistance is easily reduced. It is preferably 0 or more, 0.03 or more, 0.05 or more, 0.07 or more, 0.10 or more, 0.15 or more, 0.18 or more, and especially 0.2 or more. 2 O] / [Li 2 O] means, using Na 2 O content divided by Li 2 The value obtained by measuring the O content.

[0073] Molar ratio ([ZnO]+[Li 2 O]+[Na 2 O]+[K 2 O]) / [Al 2 O 3 The suitable lower limit of [ZnO] is 0.5 or more, 0.55 or more, 0.60 or more, 0.7 or more, 0.75 or more, 0.8 or more, and especially 0.85 or more. 2 O]+[Na 2 O]+[K 2 O]) / [Al 2 O 3 If the molar ratio ([ZnO]+[Li 2 O]+[Na 2 O]+[K 2 O]) / [Al 2 O3 ] is too large, the efficiency of ion exchange is also likely to decrease. Therefore, the molar ratio ([ZnO]+[Li 2 O]+[Na 2 O]+[K 2 O]) / [Al 2 O 3 The upper limit range of [ZnO] is preferably 2 or less, 1.8 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.35 or less, 1.3 or less, and particularly preferably 1.25 or less. 2 O]+[Na 2 O]+[K 2 O]) / [Al 2 O 3 ] is made of ZnO, Li 2 O、Na 2 O and K 2 The total amount of O divided by Al 2 O 3 The value obtained.

[0074] Molar ratio [MgO] / [Al 2 O 3 ]is preferably 1.2 or less, 1.1 or less, 1.05 or less, 1.0 or less, 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.6 or less, and particularly 0.5 or less. 2 O 3 If [MgO] / [Al 2 O 3 The lower limit of [MgO] / [Al 2 O 3 ] means that the content of MgO is divided by the content of Al 2 O 3 The value obtained by the content.

[0075] If the molar ratio ([SiO 2 ]+[B 2 O 3 ]+[P 2 O 5 ]) / ((100×[SnO 2 ])×([Li 2 O]+[Na 2 O]+[K2 O] + [MgO] + [CaO] + [BaO] + [SrO] + [ZnO] + [Al 2 O 3 ])) range, it is possible to improve both clarity and resistance to devitrification. 2 ]+[B 2 O 3 ]+[P 2 O 5 ]) / ((100×[SnO 2 ])×([Li 2 O]+[Na 2 O]+[K 2 O] + [MgO] + [CaO] + [BaO] + [SrO] + [ZnO] + [Al 2 O 3 The suitable lower limit range of [SiO] is 0.30 or more, 0.33 or more, 0.35 or more, 0.37 or more, 0.38 or more, 0.39 or more, 0.40 or more, 0.41 or more, 0.42 or more, 0.43 or more, 0.44 or more, 0.45 or more, 0.48 or more, 0.50 or more, 0.51 or more, 0.52 or more, 0.53 or more, 0.54 or more, and especially 0.55 or more. If the molar ratio ([SiO 2 ]+[B 2 O 3 ]+[P 2 O 5 ]) / ((100×[SnO 2 ])×([Li 2 O]+[Na 2 O]+[K 2 O] + [MgO] + [CaO] + [BaO] + [SrO] + [ZnO] + [Al 2 O 3 ])) is too small, SnO 2 Crystals are easily precipitated. Molar ratio ([SiO 2 ]+[B 2 O 3 ]+[P 2 O 5 ]) / ((100×[SnO 2 ])×([Li 2 O]+[Na 2 O]+[K 2 O] + [MgO] + [CaO] + [BaO] + [SrO] + [ZnO] + [Al 2 O 3The upper limit range of ([SiO 2 ]+[B 2 O 3 ]+[P 2 O 5 ]) / ((100×[SnO 2 ])×([Al 2 O 3 ]+[Li 2 O]+[Na 2 O]+[K 2 O]+[MgO]+[CaO]+[BaO]+[SrO]+[ZnO])) is SiO 2 , B 2 O 3 and P 2 O 5 The total amount of SnO 2 The content is 100 times that of Al 2 O 3 , Li 2 O、Na 2 O.K 2 The value obtained by multiplying the total amount of O, MgO, CaO, BaO, SrO and ZnO.

[0076] ([SiO 2 ]+1.2×[P 2 O 5 ]-3×[Al 2 O 3 ]-[B 2 O 3 ]-2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]) is preferably -20 or more, -18 or more, -15 or more, -12 or more, -10 or more, -8 or more, -5 or more, -3 or more, and particularly 0 or more. 2 ]+1.2×[P 2 O 5 ]-3×[Al 2 O 3 ]-[B 2 O 3 ]-2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]) is too small, the acid resistance tends to decrease. On the other hand, ([SiO 2 ]+1.2×[P2 O 5 ]-3×[Al 2 O 3 ]-[B 2 O 3 ]-2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]) is too large, the ion exchange performance may not be fully exerted. 2 ]+1.2×[P 2 O 5 ]-3×[Al 2 O 3 ]-[B 2 O 3 ]-2×[Li 2 O]-1.5×[Na 2 O]-[K 2 The suitable upper limit range of ([SiO]) is 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, and particularly 20 or less. 2 ]+1.2×[P 2 O 5 ]-3×[Al 2 O 3 ]-[B 2 O 3 ]-2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]), is from SiO 2 The content is 1.2 times that of P 2 O 5 From the total content, subtract 3 times the Al 2 O 3 Content, B 2 O 3 content, 2 times of Li 2 O content, 1.5 times the Na 2 O content, K 2 The total amount of O content is obtained.

[0077] The following formula X value is a factor related to the exchange rate of Li ions and Na ions. If the X value is too small, the efficiency of the ion exchange between Li ions and Na ions in the molten salt is reduced, and compressive stress is difficult to enter. In particular, the stress depth (DOC) of the compressive stress layer in the ion exchange between Li ions contained in the glass and Na ions in the molten salt may become smaller. Therefore, the appropriate lower limit range of the X value is 300 or more, 320 or more, 330 or more, 340 or more, 350 or more, 400 or more, 450 or more, 460 or more, 480 or more, 500 or more, 520 or more, and especially 550 or more. The upper limit range of X is not particularly limited, for example, 850 or less, 800 or less.

[0078] X=-1.49×[SiO 2 ]+26.98×[Al 2 O 3 ]-3.23×[B 2 O 3 ]+48.56×[Li 2 O]-24.31×[Na 2 O]-0.28×[MgO]+2.74×[CaO]

[0079] The W value in the following formula is a factor related to Young's modulus. If the W value is too small, the Young's modulus becomes low and the glass is easily broken. Therefore, the appropriate lower limit range of the W value is 250 or more, 300 or more, 330 or more, 340 or more, 350 or more, 360 or more, 370 or more, 400 or more, 430 or more, 450 or more, 480 or more, and particularly 500 or more. The upper limit range of the W value is not particularly limited, for example, 750 or less, 700 or less.

[0080] W=0.07×[SiO 2 ]+18.17×[Al 2 O 3 ]-4.42×[B 2 O 3 ]+41.43×[Li 2 O]-29.30×[Na 2 O]+1.43×[MgO]-10.43×[CaO]

[0081] In addition to the above-mentioned components, for example, the following components may be added.

[0082] TiO 2 It is a component that improves ion exchange performance and reduces high temperature viscosity, but if its content is too high, transparency and resistance to devitrification are likely to decrease. 2Suitable contents of are 0 to 10%, 0 to 5%, 0 to 3%, 0 to 1.5%, 0 to 1%, 0 to 0.1%, and especially 0.001 to 0.1 mol %.

[0083] ZrO 2 ZrO is a component that increases the Vickers hardness and increases the viscosity and strain point near the liquidus viscosity. However, if its content is too high, the devitrification resistance may be significantly reduced. 2 Suitable contents are 0-10%, 0-5%, 0-3%, 0-1.5%, 0-1%, 0-0.5%, 0-0.4%, 0-0.3%, 0-0.2%, especially 0-0.1%.

[0084] Fe 2 O 3 It is an impurity mixed in from the raw materials. 2 O 3 The suitable upper limit range of Fe, in mole %, is 0.1% or less, 0.08% or less, 0.05% or less, 0.02% or less, less than 0.015%, less than 0.01%, less than 0.008%, and especially less than 0.005%. 2 O 3 If the content of Fe is too high, the transmittance of the cover glass is likely to decrease. On the other hand, the appropriate lower limit range, in terms of mole %, is 0.001% or more, 0.002% or more, or 0.003% or more. 2 O 3 If the content is too low, the cost of raw materials will increase due to the use of high-purity raw materials, and the product cannot be manufactured cheaply.

[0085] You can also add 0.001-1% SO 3 and / or CeO 2 As a clarifying agent.

[0086] Nd 2 O 3 ,La 2 O 3 , Y 2 O 3 , Nb 2 O 5 、 2 O 5 , Hf 2 O 3 Rare earth oxides such as , are components that increase the Young's modulus. However, the raw material cost is high, and if added in large quantities, the devitrification resistance is easily reduced. Therefore, the appropriate content of the rare earth oxide is 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, and particularly 0 to 0.1%.

[0087] The tempered glass plate (tempered glass plate) of the present invention preferably contains substantially no As as a glass composition for environmental considerations. 2 O 3 , Sb 2 O 3 , PbO and F. In addition, it is also preferred that Bi is substantially not contained for environmental considerations. 2 O 3 In the glass composition of the tempered glass plate and tempered glass plate of the present invention, the phrase "substantially contains no to" means that the indicated components are not actively added as glass components, but the addition of impurity levels is permitted, and specifically, means that the content of the indicated components is less than 0.05 mol %.

[0088] The tempered glass plate (tempered glass plate) of the present invention preferably has the following properties.

[0089] The density (ρ) is preferably 2.9 g / cm 3 Below, 2.85g / cm 3 Below, 2.83g / cm 3 Below, 2.8g / cm 3 Below, 2.75g / cm 3 Below, 2.7g / cm 3 Below, 2.35~2.65g / cm 3 , particularly preferably 2.25 to 2.6 g / cm 3 The lower the density, the lighter the tempered glass sheet can be.

[0090] The thermal expansion coefficient at 30 to 380°C is preferably 150×10 -7 / ℃ below, 100×10 -7 / ℃ below, 50~95×10 -7 / ℃, especially 40~85×10 -7 / °C. In addition, the "thermal expansion coefficient at 30 to 380°C" refers to a value obtained by measuring the average thermal expansion coefficient using a dilatometer.

[0091] The softening point (Ts) is preferably 920° C. or less, 910° C. or less, 900° C. or less, 890° C. or less, 880° C. or less, 870° C. or less, 860° C. or less, 850° C. or less, 840° C. or less, 830° C. or less, and particularly preferably 700 to 820° C. If the softening point is too high, hot workability may be reduced.

[0092] High temperature viscosity 10 2.5dPa·s is preferably 1680°C or less, 1670°C or less, 1660°C or less, 1650°C or less, 1640°C or less, 1630°C or less, 1620°C or less, 1600°C or less, 1550°C or less, 1520°C or less, 1500°C or less, and particularly 1300 to 1490°C. If the high temperature viscosity is 10 2.5 When the temperature of dPa·s is too high, the meltability and formability decrease, and it becomes difficult to form the molten glass into a sheet shape.

[0093] The liquid phase viscosity (η) is preferably 10 2.8 dPa·s or more, 10 2.9 dPa·s or more, 10 3.0 dPa·s or more, 10 3.1 dPa·s or more, 10 3.2 dPa·s or more, 10 3.3 dPa·s or more, 10 3.4 dPa·s or more, 10 3.5 dPa·s or more, 10 3.55 dPa·s or more, especially 10 3.58 dPa·s or more. In addition, the higher the liquidus viscosity, the higher the resistance to devitrification, and the less likely it is that devitrified objects will occur during molding. Here, the so-called "liquidus viscosity" refers to the value obtained by measuring the viscosity of the liquidus temperature by the platinum ball pulling method. The so-called "liquidus temperature" is the highest temperature at which devitrification (devitrified objects) can be confirmed inside the glass after glass powder that passes through a 30-mesh (500μm) standard sieve and remains on a 50-mesh (300μm) sieve is placed in a platinum dish and kept in a temperature gradient furnace for 24 hours. The platinum dish is taken out and observed under a microscope.

[0094] The transmittance at a wavelength of 400 nm and a thickness of 0.6 mm is preferably 85% or more, 88% or more, and particularly 90% or more. If the transmittance is low, the visibility and color expression of the display may be reduced when used for cover glass. The upper limit of the transmittance is not particularly limited, but is actually below 100%.

[0095] In the present invention, the mechanical properties mainly refer to properties related to glass strength determined by the glass composition, and specifically include properties such as Young's modulus and fracture toughness value.

[0096] The Young's modulus (E) is preferably 76 GPa or more, 77 GPa or more, 78 GPa or more, 79 GPa or more, 80 GPa or more, and particularly 82 GPa or more. If the Young's modulus is low, the cover glass is easily bent when the plate thickness is thin. In addition, the upper limit range of the Young's modulus is not particularly limited, but is actually below 150 GPa. In addition, the "Young's modulus" can be calculated by the well-known resonance method.

[0097] The fracture toughness K1c is preferably 0.78 MPa·m 0.5 Above, 0.79MPa·m 0.5 Above, 0.80MPa·m 0.5 Above, 0.81MPa·m 0.5 Above, particularly preferably 0.82 MPa·m 0.5 If the fracture toughness K1c is low, the tempered glass plate is easily broken. The upper limit of the fracture toughness K1c is not particularly limited, but is practically 3 MPa·m 0.5 the following.

[0098] In the present invention, strengthening characteristics refer to characteristics related to the strength of glass that are subsequently imparted to the formed glass through ion exchange treatment, and specifically include characteristics such as the compressive stress value (CS) at the outermost surface of the glass, the compressive stress value (CS30) at a depth of 30 μm from the outermost surface, the stress depth (DOC), and the internal tensile stress value (CTcv).

[0099] In the tempered glass plate of the present invention, the outermost compressive stress value (CS) during ion exchange between Li ions contained in the glass and Na ions in the molten salt is preferably 240 MPa or more, 260 MPa or more, 280 MPa or more, 300 MPa or more, 320 MPa or more, 340 MPa or more, 350 MPa or more, 380 MPa or more, 400 MPa or more, 420 MPa or more, and particularly 450 MPa or more. The larger the outermost compressive stress value (CS), the higher the strength. On the other hand, if a very large compressive stress is formed on the surface, the tensile stress (CT) inside the tempered glass plate will increase. CV ) is extremely high, which leads to explosive bursting when damaged. In addition, the dimensional change before and after the ion exchange treatment may increase. Therefore, the compressive stress value (CS) of the outermost surface is preferably 1200MPa or less, 1000MPa or less, 900MPa or less, 850MPa or less, 800MPa or less, 780MPa or less, 750MPa or less, and especially 740MPa or less.

[0100] The compressive stress value (CS30) at a depth of 30μm from the outermost surface in the ion exchange between Li ions contained in the glass and Na ions in the molten salt is preferably 25MPa or more, 30MPa or more, 35MPa or more, 40MPa or more, 50MPa or more, 60MPa or more, 70MPa or more, 80MPa or more, 90MPa or more, 100MPa or more, 105MPa or more, 110MPa or more, 115MPa or more, and especially 120MPa or more. The larger the compressive stress value (CS30) at a depth of 30μm, the higher the strength. In addition, CS30 can effectively improve the characteristics of the scratch four-point bending strength in particular. On the other hand, if a maximum compressive stress is formed at a depth of 30μm, the tensile stress (CT CV ) becomes extremely high, which leads to explosive bursting when damaged. In addition, the dimensional change before and after the ion exchange treatment may increase. Therefore, the compressive stress value (CS30) at a depth of 30μm is preferably 400MPa or less, 350MPa or less, 330MPa or less, 300MPa or less, 280MPa or less, 270MPa or less, 260MPa or less, and particularly 250MPa or less.

[0101] The stress depth (DOC) in the ion exchange between the Li ions contained in the glass and the Na ions in the molten salt is preferably 3 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, and especially 50 μm or more. The deeper the stress depth, the more difficult it is for protrusions and sand particles on the road surface to reach the tensile stress layer when the smartphone falls, which can reduce the probability of breakage of the cover glass. On the other hand, if the stress depth is too deep, the dimensional change before and after the ion exchange treatment may increase. In addition, the compressive stress value of the outermost surface tends to decrease. Therefore, the stress depth (DOC) is preferably 200 μm or less, 180 μm or less, 170 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 110 μm or less, and especially 100 μm or less. Furthermore, if the ion exchange time is prolonged or the temperature of the ion exchange solution is increased, the stress depth tends to become deeper.

[0102] The internal tensile stress value (CTcv) during the ion exchange between Li ions contained in the glass and Na ions in the molten salt is preferably 88 MPa or less, 85 MPa or less, 80 MPa or less, 75 MPa or less, 73 MPa or less, 70 MPa or less, 68 MPa or less, 65 MPa or less, 62 MPa or less, and particularly 60 MPa or less. If the internal tensile stress value is too large, the tempered glass sheet may explode due to point impact, or the glass may shatter explosively when it explodes. The lower limit range of the internal tensile stress value (CTcv) is not particularly limited, but is actually 5 MPa or more.

[0103] In the tempered glass plate of the present invention, the mass loss per unit surface area after being immersed in a 5 mass % HCl aqueous solution heated to 80° C. for 24 hours is preferably 2.0 mg / cm 2 Below, 1.5mg / cm 2 Below, 1.0mg / cm 2 Below, 0.9mg / cm 2 Below, 0.8mg / cm 2 Below, 0.7mg / cm 2 Below, 0.6mg / cm 2 Below, 0.5mg / cm 2 Below, 0.4mg / cm 2 Below, 0.3mg / cm 2 Below, 0.2mg / cm 2 Below, especially 0.1mg / cm 2 The tempered glass plate may come into contact with an acidic chemical solution depending on the use environment of the device, and preferably has high acid resistance from the viewpoint of preventing device failure.

[0104] Furthermore, the mass loss per unit surface area after immersion in a 5 mass % NaOH aqueous solution heated to 80° C. for 6 hours is preferably 5.0 mg / cm 2 Below, 4.5mg / cm 2 Below, 4.0mg / cm 2 Below, 3.5mg / cm 2 Below, 3.0mg / cm 2 Below, 2.5mg / cm 2 Below, 2.0mg / cm 2 Below, 1.5mg / cm 2 Below, especially 1.0 mg / cm 2 The tempered glass plate may come into contact with alkaline chemical liquids or detergents depending on the use environment of the device, and therefore is required to have high alkali resistance.

[0105] Furthermore, the mass loss per unit surface area after immersion in a 10 mass % HF aqueous solution maintained at 20° C. for 20 minutes is preferably 30 mg / cm 2 Below, 25mg / cm 2 Below, 20mg / cm 2 Below, 15mg / cm 2 Below, 14mg / cm 2 Below, 13mg / cm 2 Below, 12mg / cm 2 Below, 11mg / cm 2 Below, 10.5mg / cm 2 Below, 10mg / cm 2 Below, 9.5mg / cm 2 Below, 9.0mg / cm 2 Below, 8.5mg / cm 2 Below, 8.0mg / cm 2 Below, 7.5mg / cm 2 Below, 7.0mg / cm 2 Below, 6.5mg / cm 2 Below, 6.0mg / cm 2 Below, 5.5mg / cm 2 Below, 5.0mg / cm 2 Below, 4.5mg / cm 2 Below, especially 4.0mg / cm 2 The tempered glass plate is sometimes subjected to chemical etching for the purpose of adjusting the thickness or modifying the surface state. In this case, it is also preferred that the tempered glass plate has high hydrofluoric acid resistance. If the tempered glass plate has high hydrofluoric acid resistance, the glass surface after chemical etching can be made to have fewer micro-concavities and convexities, and high strength can be obtained.

[0106] In the present invention, mechanical strength refers to the strength characteristics of glass determined by the mechanical characteristics and strengthening characteristics of glass, and specifically includes scratched four-point bending strength.

[0107] The tempered glass plate of the present invention preferably has a scratched four-point bending strength of 150 MPa or more, 160 MPa or more, 1170 MPa or more, 180 MPa or more, 190 MPa or more, 200 MPa or more, 220 MPa or more, 240 MPa or more, and particularly preferably 265 MPa or more. If the scratched four-point bending strength is too low, it is easy to crack when dropped when used as a cover glass of a smartphone. In addition, the upper limit of the scratched four-point bending strength is not particularly limited, but is actually below 1500 MPa.

[0108] In the tempered glass plate of the present invention, the plate thickness is preferably 2.0 mm or less, 1.5 mm or less, 1.3 mm or less, 1.1 mm or less, 1.0 mm or less, 0.9 mm or less, and particularly 0.85 mm or less. The smaller the plate thickness, the lower the mass of the tempered glass plate. On the other hand, if the plate thickness is too thin, it is difficult to obtain the desired mechanical strength. Therefore, the plate thickness is preferably 0.01 mm or more, 0.02 mm or more, 0.03 mm or more, 0.05 mm or more, 0.1 mm or more, 0.2 mm or more, 0.3 mm or more, 0.35 mm or more, 0.4 mm or more, 0.45 mm or more, 0.5 mm or more, 0.55 mm or more, 0.6 mm or more, 0.65 mm or more, and particularly 0.7 mm or more. In addition, the thickness of the tempered glass plate can also be in the same range. In addition, the thickness of the tempered glass plate can be selected according to the application. For example, if it is used for non-folding display applications, the thickness is preferably 0.35 to 0.85 mm, more preferably 0.45 to 0.75 mm, 0.51 to 0.71 mm. On the other hand, in the case of foldable display applications, it is preferably 0.01 to 0.10 mm, more preferably 0.02 to 0.05 mm, 0.025 to 0.04 mm.

[0109] In addition, in the tempered glass plate of the present invention, when high transmittance is emphasized, it is preferred that substantially no crystals are contained. Here, “substantially no crystals” means that the content of crystals in the glass is 0.01 mass % or less. On the other hand, when higher mechanical properties are emphasized, no crystals may be contained.

[0110] The method for producing a tempered glass plate of the present invention is characterized by comprising the following steps: a step of preparing a tempered glass plate, wherein the tempered glass plate contains SiO 2 50~80%,Al 2 O 3 1~25%, B 2 O 3 0~15%,Li 2 O 1~20%, Na 2 O 0~25%, K 2 O 0~20%, ZnO 0~10%, P 2 O 5 0~15%, ZrO 2 0~10%, SnO 2 0~0.30%,[Li 2 O]+[Na 2 O] 1~30%,[Li 2O] + [MgO] 1 to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.1 to 30%; and an ion exchange step of performing ion exchange on the strengthened glass plate to obtain a strengthened glass plate having a compressive stress layer on the surface. The method for manufacturing a strengthened glass plate of the present invention includes not only a case where the ion exchange treatment is performed only once, but also a case where the ion exchange treatment is performed multiple times.

[0111] The method for manufacturing a tempered glass plate is as follows. First, glass raw materials prepared according to a desired glass composition are preferably put into a continuous melting furnace, heated and melted at 1400 to 1700°C, clarified, and then the molten glass is supplied to a forming device to be formed into a plate shape and cooled. After forming into a plate shape, the method of cutting into a predetermined size can adopt a well-known method.

[0112] As a method for forming molten glass into a plate-like shape, an overflow down-draw method is preferred. When the overflow down-draw method is used, there is an overflow converging surface in the central part of the plate thickness direction, and the surface that should be the surface of the glass plate does not contact the surface of the forming body refractory, and is formed into a plate-like shape in the state of a free surface. Therefore, a glass plate with good surface quality can be manufactured cheaply without grinding. In addition, when the overflow down-draw method is used, an alumina refractory and a zirconia refractory are used as the forming body refractory. And the tempered glass plate of the present invention (tempered glass plate) has good adaptability with alumina refractory and zirconia refractory (particularly alumina refractory), so it has the property of being difficult to react with these refractory materials to generate foam or products.

[0113] In addition to the overflow down-draw method, various forming methods can be used, such as the float method, the down-draw method (the flow hole down-draw method, the re-draw method, etc.), the flattening method, the pressing method, and the like.

[0114] In the tempered glass sheet and tempered glass sheet of the present invention, not only a flat plate shape but also a shape formed into a plate shape and then given a three-dimensional shape by bending or the like is included.

[0115] When forming the molten glass, it is preferred to cool the molten glass at a cooling rate of 3°C / min or more and less than 1000°C / min in the temperature range between the slow cooling point and the strain point. The lower limit of the cooling rate is preferably 10°C / min or more, 20°C / min or more, 30°C / min or more, and particularly preferably 50°C / min or more. The upper limit is preferably less than 1000°C / min, less than 500°C / min, and particularly preferably less than 300°C / min. If the cooling rate is too fast, the structure of the glass becomes rough, and it is difficult to increase the Vickers hardness after ion exchange treatment. On the other hand, if the cooling rate is too slow, the production efficiency of the glass sheet is reduced.

[0116] In the method for producing tempered glass of the present invention, when high transmittance is important, it is preferred to avoid crystallization of the tempered glass plate. On the other hand, when higher mechanical properties are important, the tempered glass plate may be crystallized by heat treating it.

[0117] In the method for producing a tempered glass sheet of the present invention, it is preferred to use NaNO 3 With KNO 3 The ion exchange treatment is performed by immersing the glass sheet in a mixed molten salt once. If the ion exchange treatment is performed, the compressive stress value (CS) at the outermost surface and the compressive stress value (CS30) at a depth of 30 μm from the outermost surface can be effectively controlled. Therefore, the tensile stress value (CT CV ) becomes too high, making it easier to obtain a safe tempered glass plate with fewer fragments when dropped. Figure 1 Schematic diagram of stress distribution of a tempered glass sheet (stress distribution in the thickness direction of the glass sheet) in which Li ions have undergone ion exchange with Na ions in a molten salt. The solid line indicates stress distribution due to NaNO 3 The dotted line represents the tempered glass plate tempered with 100% by mass of the tempering molten salt. 3 , 90% KNO 3 Stress distribution of tempered glass sheets strengthened by mixed molten salts. Figure 1 It can be seen that the solid line shows the NaNO 3 100% by mass tempered glass plate, CS is 498MPa, CS30 is 265MPa, CT CV is 91 MPa. In contrast, the dotted line shows the NaNO 3 With KNO 3 The CS of the tempered glass plate strengthened by the mixed molten salt is suppressed to 425MPa and the CS30 is suppressed to 241MPa. As a result, CT CV It is also as small as 87MPa.

[0118] NaNO used in the ion exchange process 3 With KNO 3 In the mixed molten salt, NaNO 3 The concentration of NaNO is preferably 0.5 mass % or more, 1 mass % or more, 5 mass % or more, 7 mass % or more, 10 mass % or more, and particularly 12 to 20 mass %. 3 If the concentration of NaNO is too low, it may be difficult to measure stress using the surface stress meter SLP-2000. 3If the concentration of is too high, the compressive stress value formed when the Li ions contained in the glass are ion-exchanged with the Na ions in the molten salt may become too high.

[0119] Furthermore, if priority is given to further increasing the compressive stress value at the outermost surface (CS) and the compressive stress value at a depth of 30 μm from the outermost surface (CS30) to obtain a tempered glass sheet with high mechanical strength and more resistance to breakage, NaNO 3 Ion exchange is performed by immersing the steel in 100 mass % of molten salt.

[0120] In addition, the tempered glass plate contains Na 2 O, it can also be immersed in KNO 3 In 100 mass % of the molten salt, ion exchange of Na ions in the glass and K ions in the molten salt is performed.

[0121] In the ion exchange step, the temperature of the molten salt is preferably 360 to 430° C., and the ion exchange time is preferably 30 minutes to 6 hours.

[0122] Example 1

[0123] The present invention will be described below based on examples. The following examples are merely illustrative and the present invention is not limited to the following examples.

[0124] (Example 1)

[0125] Tables 1 to 50 show the glass compositions and glass properties of the examples (samples No. 1 to 23, 26 to 320) and comparative examples (samples No. 24 and 25) of the present invention. NA means not measured. 2 O represents Li 2 O、Na 2 O and K 2 O, and RO represents the total amount of MgO, CaO, SrO and BaO.

[0126]

Table 1

[0127]

[0128]

Table 2

[0129]

[0130]

Table 3

[0131]

[0132]

Table 4

[0133]

[0134]

Table 5

[0135]

[0136]

Table 6

[0137]

[0138]

Table 7

[0139]

[0140]

Table 8

[0141]

[0142]

Table 9

[0143]

[0144]

Table 10

[0145]

[0146]

Table 11

[0147]

[0148]

Table 12

[0149]

[0150]

Table 13

[0151]

[0152]

Table 14

[0153]

[0154]

Table 15

[0155]

[0156]

Table 16

[0157]

[0158]

Table 17

[0159]

[0160]

Table 18

[0161]

[0162]

Table 19

[0163]

[0164]

Table 20

[0165]

[0166]

Table 21

[0167]

[0168]

Table 22

[0169]

[0170]

Table 23

[0171]

[0172]

Table 24

[0173]

[0174]

Table 25

[0175]

[0176]

Table 26

[0177]

[0178]

Table 27

[0179]

[0180]

Table 28

[0181]

[0182]

Table 29

[0183]

[0184]

Table 30

[0185]

[0186]

Table 31

[0187]

[0188]

Table 32

[0189]

[0190]

Table 33

[0191]

[0192]

Table 34

[0193]

[0194]

Table 35

[0195]

[0196]

Table 36

[0197]

[0198]

Table 37

[0199]

[0200]

Table 38

[0201]

[0202]

Table 39

[0203]

[0204]

Table 40

[0205]

[0206]

Table 41

[0207]

[0208]

Table 42

[0209]

[0210]

Table 43

[0211]

[0212]

Table 44

[0213]

[0214]

Table 45

[0215]

[0216]

Table 46

[0217]

[0218]

Table 47

[0219]

[0220]

Table 48

[0221]

[0222]

Table 49

[0223]

[0224]

Table 50

[0225]

[0226] Samples No. 1 to 320 in Tables 1 to 50 were prepared as follows. First, glass raw materials were prepared according to the glass compositions of Samples No. 1 to 320 in Tables 1 to 25, and melted at 1600° C. for 21 hours using a platinum dish. Next, the obtained molten glass was poured onto a carbon plate, formed into a flat plate shape, and then cooled at 3° C. / min in a temperature range from the slow cooling point to the strain point to obtain a glass plate (glass plate for strengthening). The various properties described in Tables 26 to 50 were evaluated for the obtained glass plates.

[0227] The density (ρ) is a value measured by the well-known Archimedean method.

[0228] Thermal expansion coefficient (α) at ​​30-380°C 30-380℃ ), is the value obtained by measuring the average thermal expansion coefficient using a dilatometer.

[0229] The softening point (Ts) is a value measured based on the method of ASTM C338.

[0230] High temperature viscosity 10 2.5 dPa·s Temperature (10 2.5 dPa·s) is the value measured by the platinum ball pulling method.

[0231] Young's modulus (E) is calculated by a method based on JIS R1602-1995 "Test method for elastic modulus of precision ceramics".

[0232] Next, both surfaces of Samples Nos. 1 to 24 and 26 to 320 were optically polished, and after the thickness reached 0.6 mm, the transmittance was measured.

[0233] The transmittance at a wavelength of 400 nm is a value obtained by measuring the linear transmittance in the thickness direction of a tempered glass plate having a thickness of 0.6 mm using an ultraviolet-visible-near-infrared spectrophotometer (UH4150 manufactured by Hitachi High-Technologies Corporation).

[0234] Furthermore, the tempered glass plates of Samples No. 1 to 24 were heated to 380°C in NaNO 3 Immerse in molten salt for 1 hour to perform ion exchange treatment. After the ion exchange treatment, clean the surface of each sample. Next, based on the phase difference distribution curve observed using the scattered light photoelastic stress meter SLP-2000 (manufactured by Orihara Seisakusho Co., Ltd.), calculate the compressive stress value (CS) at the outermost surface, the compressive stress value at a depth of 30μm (CS30), the stress depth (DOC) and the internal tensile stress value (CTcv). Here, DOC is the depth at which the stress value becomes 0. In addition, by subjecting the obtained tempered glass plates of sample No. 26 to 320 to 380°C KNO 3 Immerse in molten salt for 4 hours and perform ion exchange treatment. Wash the surface of each sample after the ion exchange treatment. Next, based on the phase difference distribution curve observed using the surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.), calculate the compressive stress value (CS) at the outermost surface, the compressive stress value at a depth of 30μm (CS30), the stress depth (DOC), and the internal tensile stress value (CTcv). Here, DOC is the depth at which the stress value becomes 0. In the calculation, the refractive index of each sample was 1.53, and the optical elastic constant was 29.0 [(nm / cm) / MPa]. In addition, although the glass composition of the surface layer of the glass is microscopically different before and after the ion exchange treatment, the glass composition as a whole is essentially the same.

[0235] In addition, sample No. 25 was subjected to optical polishing on both surfaces to a plate thickness of 0.6 mm, and then subjected to heat treatment at 615°C for 12 hours and 850°C for 3 hours to precipitate crystals to form crystallized glass. The Young's modulus and transmittance of the obtained crystallized glass were measured under the above conditions. 3 The samples were immersed in the molten salt for 6 hours to perform an ion exchange treatment. After the ion exchange treatment, the surface of each sample was washed.

[0236] The tempered glass plates of Samples Nos. 1 to 320 obtained in the above manner were evaluated for acid resistance, alkali resistance, hydrofluoric acid resistance, and fracture toughness value (K1c).

[0237] In the acid resistance test, a double-sided mirror-polished glass sample with a size of 50×10×1.0 mm was used as a measurement sample. After being thoroughly cleaned with a neutral detergent and pure water, it was immersed in a 5 mass % HCl aqueous solution heated to 80°C for 24 hours, and the mass loss per unit surface area (mg / cm) before and after the immersion was calculated. 2 ) for evaluation.

[0238] In the alkali resistance test, a double-sided mirror-polished glass sample with a size of 50×10×1.0 mm was used as a measurement sample. After being thoroughly cleaned with a neutral detergent and pure water, it was immersed in a 5 mass % NaOH aqueous solution heated to 80°C for 6 hours, and the mass loss per unit surface area (mg / cm) before and after the immersion was calculated. 2 ) for evaluation.

[0239] In the hydrofluoric acid resistance test, a glass sample with a size of 50×10×1.0 mm and double-sided mirror polishing was used as a measurement sample. After being thoroughly cleaned with a neutral detergent and pure water, it was immersed in a 10 mass % HF aqueous solution maintained at 20°C for 20 minutes, and the mass loss per unit surface area (mg / cm) before and after the immersion was calculated. 2 ) for evaluation.

[0240] The fracture toughness value (K1c) was measured by the SEPB method based on JIS R1607 "Test method for fracture toughness of fine ceramics". The fracture toughness value of each sample was calculated as the average value of three points.

[0241] As shown in Tables 1 to 30, the Young's modulus of samples No. 1 to 23 and 26 to 65 is high, and the fracture toughness value of No. 1 is 0.82 MPa·m 0.5 , a glass with high mechanical properties can be obtained. On the other hand, the comparative sample No. 24 has a low Young's modulus of 74 GPa and a fracture toughness value of 0.76 MPa·m due to the small amount of RO. 0.5 In addition, the transmittance of samples No. 1 to 23 was as high as 91.2% or more. On the other hand, the transmittance of sample No. 25, which was a crystallized tempered glass plate, after crystallization was as low as 72.5%.

[0242] (Example 2)

[0243] Table 51 shows the glass properties of Example A of the present invention and Comparative Example B. Here, "SPP-4PB" means scratch four-point bending strength, and "NA" means not measured.

[0244]

Table 51

[0245]

[0246] Example A and Comparative Example B (tempered glass plate) of Table 51 were prepared as follows. First, glass raw materials were prepared according to the glass compositions of Samples No. 1 and 24 listed in Tables 1 and 2, and melted at 1600°C for 21 hours using a platinum dish. Thereafter, the obtained molten glass was flowed onto a carbon plate, formed into a flat plate shape and slowly cooled. For the obtained glass plate, the Young's modulus was evaluated by the same method as in Example 1. Thereafter, a tempered glass plate having a plate thickness of 0.6 mm was obtained by grinding and polishing the obtained flat-plate-shaped glass. Next, the obtained tempered glass plates were cut into specified sizes. In addition, the tempered glass plate of Example A contains 15 mass % of NaNO at 430°C. 3 , 85 mass% KNO 3 The tempered glass plate of Comparative Example B was immersed in a mixed molten salt of NaNO for 1 hour to perform ion exchange treatment to obtain a tempered glass plate. 3 After being immersed in molten salt for 3 hours to perform ion exchange treatment, the 3 , 5 mass% NaNO 3 The glass sheet was immersed in a mixed molten salt of for 45 minutes to perform ion exchange treatment to obtain a strengthened glass sheet.

[0247] The obtained strengthened glass plate was measured for fracture toughness value and scratched four-point bending strength.

[0248] The fracture toughness value (K1c) was evaluated by the same method as in Example 1.

[0249] The scratched four-point bending strength is carried out in the following procedure. First, the glass is damaged in the following procedure. A tempered glass plate processed to a size of 35mm×35mm and a thickness of 0.6mm is fixed in a vertical state on a 1.5mm thick SUS plate, and the front end of the pendulum-shaped arm is hit against it through P180 sandpaper to cause damage. The front end of the arm is an iron cylinder with a diameter of φ5mm, and the arm weight is 550g. The arm is swung down at a height of 100mm from the impact point. Then, the damaged sample is subjected to a four-point bending test in accordance with JIS R1601 (1995) to measure the "scratched four-point bending strength". In each embodiment, 6 samples are tested, and the average of their measured values ​​is used as the evaluation result.

[0250] It can be seen from Table 51 that Example A has high mechanical properties, with a Young's modulus of 87 GPa and a fracture toughness value of 0.82 MPa·m 0.5The compressive stress value (CS30) at a depth of 30 μm from the outermost surface of the compressive stress layer is as high as 244 MPa, so the scratch four-point bending strength is as high as 290 MPa. On the other hand, the Young's modulus of Comparative Example B is 74 GPa and the fracture toughness value is 0.76 MPa·m lower than that of Example A. 0.5 Moreover, CS30 is as low as 120MPa, so the scratch four-point bending strength is also as low as 172MPa.

[0251] (Example 3)

[0252] Glass raw materials were prepared according to the glass compositions of samples No. 73 and No. 304 listed in the table, and melted at 1600°C for 21 hours using a platinum dish. The molten glass was then poured onto a carbon plate, formed into a flat plate and slowly cooled. The flat plate-shaped glass obtained was ground and polished to obtain a plate-shaped glass with a thickness of 0.3 mm. The plate was then thinned using a hydrofluoric acid etching process to obtain a strengthened glass plate with a thickness of 31 μm. Next, the strengthened glass plates obtained were cut into sizes of 50 mm × 50 mm. In addition, the strengthened glass plate of sample No. 73 was subjected to a KNO treatment at 380°C. 3 The glass plate was immersed in a molten salt for 1 hour and 10 minutes to perform ion exchange treatment to obtain a strengthened glass plate. 3 The glass was immersed in a molten salt for 1 hour and 45 minutes to perform an ion exchange treatment to obtain a strengthened glass plate. In addition, the obtained strengthened glass plate was thinned by an etching process using hydrofluoric acid to obtain a measurement sample with a plate thickness of 30 μm. The compressive stress value of the measurement sample No. 73 was 698 MPa, and the depth of the compressive stress layer was 5.5 μm. The compressive stress value of the measurement sample No. 304 was 418 MPa, and the depth of the compressive stress layer was 4.8 μm.

[0253] The surface roughness and impact strength of the test specimens were measured.

[0254] The surface roughness was measured using a scanning white light interferometer (New View 7300 manufactured by Zygo Corporation) and was calculated as the “arithmetic mean height” in accordance with ISO 25178. The detailed measurement conditions are as follows.

[0255] Device name: Zygo Corporation New View 7300

[0256] Field of view: 73.55μm×55.16μm

[0257] Objective lens: 50 times

[0258] Zoom lens: 2x

[0259] Analysis software: Metro Pro (manufactured by Zygo Corporation)

[0260] Shape Modification: Plane (1 time)

[0261] Filter Type: Gauss Spline

[0262] Filter Low Wavelength (high pass): 13.8μm

[0263] Filter High Wavelength (low pass): 0.345μm

[0264] The impact resistance is measured by the following impact resistance test. First, the obtained measurement sample (size 50mm×50mm when viewed from above) is placed on a stone platform, and the front end of the spherical impact body (ball head diameter 0.7mm, total mass 5.4g ballpoint pen: BIC, orange EG0.7) is dropped on the glass sample for testing. At this time, the front end of the impact body is dropped vertically relative to the glass sample, and the impact body is passed through the inner hole of the vertical guide cylinder until it falls on the glass sample. The height of the front end of the impact body before falling is used as the falling height, and its initial value is set to 1.0cm and it is dropped. When the drop does not cause the glass sample to break, the height is raised by 0.5cm, and it is dropped again. In this way, the attempts to increase and drop the drop height are repeated until the glass sample is broken, and the drop height when the glass sample is broken is obtained as the damage height.

[0265] Sample No. 73 had a surface roughness of 0.24 nm and a fracture height of 10.5 cm, while Sample No. 304 had a surface roughness of 0.31 nm and a fracture height of 10.7 cm.

[0266] Industrial Applicability

[0267] The tempered glass plate of the present invention is suitable as a cover glass for a touch panel display of a mobile phone, a digital camera, a PDA (mobile terminal), etc. In addition, in addition to these uses, the tempered glass plate of the present invention can also be expected to be used in uses requiring high mechanical strength, such as window glass, a substrate for a magnetic disk, a substrate for a flat panel display, a substrate for a flexible display, a cover glass for a solar cell, a cover glass for a solid-state imaging element, and a cover glass for a vehicle.

Claims

1. A tempered glass plate having a compressive stress layer on the surface, characterized in that: The glass composition includes, by mol%, SiO2 50% to 85%, Al2O3 1% to 25%, B2O3 0% to 15%, Li2O 0% to 20%, Na2O 0% to 25%, K2O 0% to 20%, ZnO 0% to 10%, P2O5 0% to 15%, ZrO2 0% to 10%, SnO2 0% to 0.30%, [Li2O] + [Na2O] 1% to 30%, [Li2O] + [MgO] 1% to 25%, and [MgO] + [CaO] + [SrO] + [BaO] 0.5% to 30%.

2. The tempered glass sheet according to claim 1, wherein: In the tempered glass plate having a compressive stress layer on the surface, the glass composition contains, in mol%, SiO2 52% to 80%, Al2O3 11.5% to 25%, B2O3 0% to 15%, Li2O 7% to 20%, Na2O 0.5% to 25%, K2O 0% to 20%, MgO 0% to 20%, CaO 0% to 10%, SrO 0% to 10%, BaO 0% to 10%, ZnO 0% to 10%, P2O5 0% to 15%, ZrO2 0% to 10%, SnO2 0% to 0.30%, and [MgO] + [CaO] + [SrO] + [BaO] 6.5% to 30%.

3. The tempered glass sheet according to claim 2, wherein: The glass composition contains MgO, and the content of MgO is 6.5 mol % to 20 mol %.

4. The tempered glass sheet according to claim 1 or 2, wherein: The molar ratio [RO] / [R2O] is 0.5 to 1.

5.

5. The tempered glass sheet according to claim 1 or 2, wherein: It contains substantially no crystals, and has a transmittance of 85% or more at a wavelength of 400 nm when converted to a thickness of 0.6 mm.

6. The tempered glass plate according to claim 1 or 2, wherein: Fracture toughness K1c is 0.78MPa·m 0.5 above.

7. The tempered glass sheet according to claim 1 or 2, wherein: The Young's modulus is 76 GPa or more.

8. The tempered glass sheet according to claim 1 or 2, wherein: It is a plate with a thickness of 0.01mm to 2.0mm. The compressive stress value CS of the outermost surface of the compressive stress layer is 200 MPa to 1200 MPa, and the stress depth DOC of the compressive stress layer is 3 μm to 200 μm.

9. The tempered glass sheet according to claim 8, wherein: It is a plate with a thickness of 0.35mm to 2.0mm. The stress depth DOC of the compressive stress layer is 50 μm to 170 μm, and the compressive stress value CS30 at a depth of 30 μm from the outermost surface is 25 MPa to 400 MPa.

10. The tempered glass sheet according to claim 1 or 2, wherein: High temperature viscosity 10 2.5 dPa·s is 1680°C or less.

11. The tempered glass plate according to claim 1 or 2, wherein: The glass composition contains Cl, and the Cl content is 0.02 mol % or more.

12. The tempered glass sheet according to claim 1 or 2, wherein: The glass composition contains MoO 3 , and the content of MoO 3 is 0.0001 mol % or more.

13. The tempered glass sheet according to claim 1, wherein: In the tempered glass plate having a compressive stress layer on the surface, the glass composition contains, in mol%, SiO2 60% to 70%, Al2O3 3% to 20%, B2O3 0% to 1%, Li2O 0% to 10%, Na2O 10% to 25%, K2O 0% to 5%, MgO 5% to 20%, CaO 0% to 1%, SrO 0% to 10%, BaO 0% to 10%, ZnO 0% to 10%, P2O5 0% to 4.7%, and [MgO] + [CaO] + [SrO] + [BaO] 5% to 30%.

14. The tempered glass sheet according to claim 1, wherein: In the tempered glass plate having a compressive stress layer on the surface, the glass composition contains, in mol%, SiO2 65% to 82%, Al2O3 5% to 16%, B2O3 0% to 10%, Li2O 0% to 10%, Na2O 5% to 25%, K2O 0% to 5%, MgO 0% to 10%, CaO 0% to 6%, SrO 0% to 5%, BaO 0% to 5%, ZnO 0% to 10%, P2O5 0% to 4.7%, [Li2O] + [Na2O] 5% to 20%, [MgO] + [CaO] + [SrO] + [BaO] 1% to 10%.

15. A method for manufacturing a tempered glass plate, characterized in that: The method comprises the following steps: a preparation step of preparing a tempered glass plate, wherein the tempered glass plate contains, as a glass composition, in mol %, SiO2 50% to 85%, Al2O3 1% to 25%, B2O3 0% to 15%, Li2O 0% to 20%, Na2O 0% to 25%, K2O 0% to 20%, ZnO 0% to 10%, P2O5 0% to 15%, ZrO2 0% to 10%, SnO2 0% to 0.30%, [Li2O] + [Na2O] 1% to 30%, [Li2O] + [MgO] 1% to 25%, [MgO] + [CaO] + [SrO] + [BaO] 0.5% to 30%; and In the ion exchange step, the tempered glass plate is subjected to an ion exchange treatment to obtain a tempered glass plate having a compressive stress layer on the surface.

16. A tempered glass plate, characterized in that: The glass composition includes, by mol%, SiO2 50% to 85%, Al2O3 1% to 25%, B2O3 0% to 15%, Li2O 0% to 20%, Na2O 0% to 25%, K2O 0% to 20%, ZnO 0% to 10%, P2O5 0% to 15%, ZrO2 0% to 10%, SnO2 0% to 0.30%, [Li2O] + [Na2O] 1% to 30%, [Li2O] + [MgO] 1% to 25%, and [MgO] + [CaO] + [SrO] + [BaO] 0.5% to 30%.

Citation Information

Patent Citations

  • Glass member

    JP2006083045A

  • Tempered glass and glass for tempering

    WO2019230889A1